Optimizing Testosterone Levels and Fertility Outcomes: A Case Series on the Impact of (Maca-OG) in Andropause and Sperm Dysfunction - Kim Ross; Corey Schuler; Marc Sklar (American Journal of Men's Health, 2024)
Low testosterone levels in men contribute to altered sexual health, including low libido, erectile dysfunction, impaired sleep, and changes in mood and energy. Nearly half of all infertility cases are implicated by male factors, such as low testosterone levels and altered semen and sperm health. The purpose of this case series is to share the experience of two men taking a concentrated, highly bioavailable gelatinized form of specific phenotypes (sometimes referred to as colors) of Lepidium peruvianum (Maca-OG™) to improve reproductive health. One man experienced an increase in total testosterone levels and fertility parameters, including sperm concentration, sperm motility, and total sperm count. The second experienced an increase in total testosterone levels, energy, mood, and sleep. This case series highlights a natural alternative for male health to support the body’s production of testosterone, especially when hormone therapy is not medically indicated or desired by the patient, or there are concerns about hormone therapy reducing the body’s production of testosterone.